2021
DOI: 10.1101/2021.02.25.21252220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing COVID-19 Airborne Transmission Risks on Public Transportation Buses: An Empirical Study on Aerosol Dispersion and Control

Abstract: This study is one of the first COVID-19 related bus studies to fully characterize cough aerosol dispersion and control in the highly turbulent real-world environment of driving regular bus routes on both a school bus and a transit bus. While several other bus studies have been conducted, they were limited to clinical contact tracing, simulation, or partial characterization of aerosol transmission in the passenger areas with constraint conditions. When considering the risk of transmission of SARS-CoV-2 (COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Research suggests that the risk of SARS-CoV-2 transmission on public transport can be substantially reduced by asking people who are unwell to refrain from its use, requiring or encouraging vaccination among passengers, changing transport schedules to reduce crowding, and improving ventilation or filtration. Buses can substantially improve ventilation by opening as many windows, doors, or roof hatches as feasible; 412 deploying recirculating-air cleaning systems that use mechanical filtration or ultraviolet germicidal irradiation; and requiring passengers to wear face masks.…”
Section: Section 2: a Review Of The Global Regional And National Resp...mentioning
confidence: 99%
“…Research suggests that the risk of SARS-CoV-2 transmission on public transport can be substantially reduced by asking people who are unwell to refrain from its use, requiring or encouraging vaccination among passengers, changing transport schedules to reduce crowding, and improving ventilation or filtration. Buses can substantially improve ventilation by opening as many windows, doors, or roof hatches as feasible; 412 deploying recirculating-air cleaning systems that use mechanical filtration or ultraviolet germicidal irradiation; and requiring passengers to wear face masks.…”
Section: Section 2: a Review Of The Global Regional And National Resp...mentioning
confidence: 99%
“… Billingsley et al (2022) point out that buses may be hot zones for the virus as many passengers enter and exit over the course of a shift and efforts to train and provide Personal Protective Equipment (PPE) for such drivers is therefore important. Simulations and experimental studies have found that increased ventilation and face masks can effectively reduce the transmission of disease in buses ( Edwards et al, 2021 ; Zhang et al, 2021 ). Systematic reviews have also shown that wearing a face mask has a great potential in controlling airborne transmitted viruses including COVID-19 ( Abboah-Offei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have implicated specific settings for SARS-CoV-2 and other respiratory infection transmission. These include school lunchrooms, restaurants, and small, private gatherings 25,146 ; classroom learning 147 ; a variety of occupational settings and worker dormitories 24 ; meat processing 148 ; religious services 149,150 ; public entertainment 151 ; buses 152,153 ; nursing homes 154 ; and fitness centers [155][156][157][158][159] . Residential settings, which typically foster extended exposure at close proximity, lend to transmission risk.…”
Section: Critical Scales and Settingsmentioning
confidence: 99%